2017
DOI: 10.1111/nup.12167
|View full text |Cite
|
Sign up to set email alerts
|

Pierre Bourdieu: Expanding the scope of nursing research and practice

Abstract: Bourdieu is an important thinker within the sociological tradition and has a philosophically sophisticated approach to theoretical knowledge and research practice. In this paper, we examine the implication of his work for nursing and the health sciences more broadly. We argue that his work is best described as a reflexive realist who provides a space for a nonpositivist approach to knowledge that does not fall into the trap of idealism or relativism. We emphasize that Bourdieu was not an abstract theorist, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 23 publications
0
36
0
5
Order By: Relevance
“…Seven research teams demonstrated that a central struggle for patients with disabilities and illnesses is the embodied knowledge of marginalization (Cowdell, ; Edwards & Imrie, ; Gibson et al., ; Kelly, ; Thibodaux, ; Townsend, ; Westergren & Lilleaas, ). This may be further exacerbated when nurses and advanced nursing practice internalize a medical paradigm and would manage a patient by controlling access to knowledge and moving the patient through the medical system as an abnormal body and not as an individual experiencing illness or disability (Collyer et al., ; Nairn & Pinnock, ; Rhynas, ). Bourdieu's theory complements the dominant mechanistic medical paradigm with an approach considering “patients’ everyday practices” in the light of their disabilities and illnesses—and can assist nurses in grasping the dual nature of everyday (health) practice in both its objective and subjective aspects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven research teams demonstrated that a central struggle for patients with disabilities and illnesses is the embodied knowledge of marginalization (Cowdell, ; Edwards & Imrie, ; Gibson et al., ; Kelly, ; Thibodaux, ; Townsend, ; Westergren & Lilleaas, ). This may be further exacerbated when nurses and advanced nursing practice internalize a medical paradigm and would manage a patient by controlling access to knowledge and moving the patient through the medical system as an abnormal body and not as an individual experiencing illness or disability (Collyer et al., ; Nairn & Pinnock, ; Rhynas, ). Bourdieu's theory complements the dominant mechanistic medical paradigm with an approach considering “patients’ everyday practices” in the light of their disabilities and illnesses—and can assist nurses in grasping the dual nature of everyday (health) practice in both its objective and subjective aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Bourdieu's theory provides nurse researchers with the possibility to elaborate a theoretically informed understanding of “patients” embodied knowledge’ or way of living that brings into consideration both objectivity and subjectivity. Patients suffering from disability and illnesses are structurally and culturally produced, and some patients may not fully understand how they as individuals fit into the bigger structure of systems of health care or the various fields of health care (Bourdieu, ; Collyer et al., ; Nairn & Pinnock, ). The concept of capital could assist nurses in understanding that human agency is complicated and reflects a combination of economic status and acquired symbolic experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations